Analysis of BUMDes Business Development Program Implementation for Village Prosperity - Machmudah, Linda; Rodiyah, Isnaini (Indonesian Journal of Cultural and Community Development, 2024)
The general background implementation of village-owned enterprises (BUMDes) is essential for promoting village prosperity through sustainable business development. The specific background this study specifically examines the operational effectiveness of BUMDes Sinar Mitra Gemilang within a local context. The knowledge gap despite the establishment of various business units, limited research evaluates the implementation strategies and outcomes of BUMDes programs, particularly regarding the challenges encountered during execution. The aims the aim of this study is to analyze the implementation of the BUMDes business development program, focusing on the factors influencing its success and the obstacles that hinder optimal performance. The results findings reveal that communication between BUMDes and the community is inadequate, human resources lack quantity despite being qualified, and community participation requires improvement. Additionally, the organizational structure is ineffective due to insufficient human resources. The novelty this study contributes to existing literature by applying Edward III's policy implementation theory and utilizing qualitative methods to provide insights into the practical aspects of BUMDes operations. The implications the implications highlight the need for enhanced communication, increased community engagement, and a stronger organizational framework to improve the overall effectiveness of BUMDes programs, ultimately aiming to enhance community welfare and ensure business sustainability. Highlights: Communication improves program effectiveness. Resource quality and quantity affect operations. Local government support enhances community engagement. Keywords: BUMDes, Implementation, Community Participation, Organizational Structure, Communication